Scaling Cloud-Based Transaction Systems: How Modern Architectures Handle Growing Demand - Varshini Choudary Nuvvula, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines how modern cloud architectures handle the scaling challenges of transaction-based systems in today's digital economy. It explores the evolution from traditional monolithic architectures to sophisticated cloud-based solutions, analyzing various scaling approaches, including vertical scaling, horizontal scaling, and autoscaling mechanisms. The article investigates key components such as load balancing, distributed databases, and implementation strategies that enable organizations to maintain high performance and reliability under growing demands. Through a detailed examination of real-world implementations, the article demonstrates how advanced cloud architectures leverage intelligent automation, predictive analytics, and distributed processing to overcome traditional scaling limitations. Special attention is given to the financial technology and e-commerce sectors, where system performance directly impacts business success. The article also addresses critical aspects of fault tolerance, disaster recovery, and cost optimization in scaled cloud environments.
Keywords: Cloud Computing Architecture; Scalability Strategies; Distributed Systems; Automated Resource Management; Performance Optimization